MODEL ARIMA UNTUK PREDIKSI CURAH HUJAN STUDI KASUS SEMARANG JATENG - A Rofik, Muchammad; Gernowo, Rahmat; Setyawan, Agus; Nursamsiah, Nursamsiah (BERKALA FISIKA, 2012)
Modeling and prediction of rainfall in 2010 in Central Java BMKG Climatological StationÂ has been done with ARIMA approach. The goal is to determine the historical pattern of the dataand then extrapolates this pattern into the future based on the assumption of continuity. Rainfalldata of 2000-2009 is a time series that can be predicted into the future using ARIMA. In thisstudy using two approaches for prediction of rainfall in 2010. The results were correlated with aprediction of rainfall data observed in 2010. Obtained a correlation of 71.1% and 75.48%.Keywords: ARIMA, rainfall, predictions, models